2022
DOI: 10.1186/s12885-022-09599-w
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between medication literacy and skin adverse reactions in non-small-cell lung cancer patients undergoing targeted EGFR-TKI therapy

Abstract: Background High medication literacy is the basis of rational medication application and is essential for the management of severe adverse drug reactions. The objective of the present study was to assess the level of medication literacy and determine the association between medication literacy and skin adverse drug reactions in non-small-cell lung cancer (NSCLC) patients undergoing targeted epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Moreover, the protracted recovery time from barrier damage is an additional contributory factor for skin disorders manifestation among Asians. 22 Previously reported risk factors for skin toxicity include age, sex, and smoking history, 23,24 but no obvious risk factors were identified in this study.…”
Section: Discussionmentioning
confidence: 70%
“…Moreover, the protracted recovery time from barrier damage is an additional contributory factor for skin disorders manifestation among Asians. 22 Previously reported risk factors for skin toxicity include age, sex, and smoking history, 23,24 but no obvious risk factors were identified in this study.…”
Section: Discussionmentioning
confidence: 70%
“…Most of the participants had good medication literacy. Compared with the medication literacy of patients with coronary heart disease (4.96±4.68) and patients with small cell lung cancer (6.54±2.78), 41,42 the medication literacy of patients with type 2 diabetes was better than both. The possible reason is that patients with type 2 diabetes are more familiar with injectable medication for diabetes, and the scenario of injectable medication for diabetes is present in the medication literacy assessment scale.…”
Section: Discussionmentioning
confidence: 85%
“…This association has not been reported in other leprosy studies; however, higher educational levels could lead to a better understanding of the occurrence of drug-related symptoms and, thus, increase the probability of a patient reporting the symptoms, as was described recently by Costa et al (2023) [ 28 ]. Other studies have shown that higher educational levels in different diseases could help medication intake and reduce ADEs [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%